2010
DOI: 10.2147/oajc.s11551
|View full text |Cite
|
Sign up to set email alerts
|

Current use of contraceptive method among women in a middle-income developing country

Abstract: Background: Jamaica is a mid-range income developing country with an increasing population and public resource constraints. Therefore, reproductive health issues are of critical importance in Jamaica. Aim: We examined the use of contraceptives among women and the factors that influence these women to use contraceptives. Materials and method: In the current study we utilized the secondary dataset for the Reproductive Health Survey, conducted by the National Family Planning Board. The investigation was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Despite these limitations, the consistency of our choice of method data with US national data for publicly funded family planning centers suggests that these findings are likely to be of considerable relevance to providers and public health policymakers, both in the US and elsewhere, who rely on similar national data sources 41. Distribution of provider-reported choice of method after the clinic visit was compared with a national provider-reported primary contraceptive method mix, in the Family Planning Annual Report 42.…”
Section: Discussionmentioning
confidence: 88%
“…Despite these limitations, the consistency of our choice of method data with US national data for publicly funded family planning centers suggests that these findings are likely to be of considerable relevance to providers and public health policymakers, both in the US and elsewhere, who rely on similar national data sources 41. Distribution of provider-reported choice of method after the clinic visit was compared with a national provider-reported primary contraceptive method mix, in the Family Planning Annual Report 42.…”
Section: Discussionmentioning
confidence: 88%
“…To increase trust, policies should focus on addressing these factors. Research literature shows a weak negative relationship between Victimization and Trust, with higher levels of Victimization reducing trust in tourism destinations [32]. However, trust tendency is not significantly affected by…”
Section: Table 11 Correlation Between Tourist Victimization and Age O...mentioning
confidence: 96%
“…It has been found that men who tend to assign contraceptive responsibility to women have more negative attitudes towards male contraceptive use [35]. The use of contraceptives among women and the factors that influence their use have been examined [4]. The factors include: being in a relationship, number of sex partners, pregnancy status, sexual activity status, age and social class.…”
Section: Related Workmentioning
confidence: 99%